2012
DOI: 10.1111/j.1365-2672.2012.05308.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis to identify genes in wine yeast adaptation to low-temperature fermentation

Abstract: Aims:  To identify genes and proteins involved in adaptation to low‐temperature fermentations in a commercial wine yeast. Methods and Results:  Nine proteins were identified as representing the most significant changes in proteomic maps during the first 24 h of fermentation at low (13°C) and standard temperature (25°C). These proteins were mainly involved in stress response and in glucose and nitrogen metabolism. Transcription analysis of the genes encoding most of these proteins within the same time frame of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
(52 reference statements)
0
14
1
Order By: Relevance
“…Only four of these genes were differentially regulated at low temperature in our data (HSP12, NSR1, RPL2B, TIR2). Salvadó et al (2012) identified ILV5 as important for the adaptation of wine yeast to low temperature fermentation; however, unlike Salvadó et al (2012), we did not see any transcriptional change in ILV5. It appears that the response to cold temperature may be strongly influenced by strain, medium and exact temperature used.…”
Section: Discussioncontrasting
confidence: 81%
“…Only four of these genes were differentially regulated at low temperature in our data (HSP12, NSR1, RPL2B, TIR2). Salvadó et al (2012) identified ILV5 as important for the adaptation of wine yeast to low temperature fermentation; however, unlike Salvadó et al (2012), we did not see any transcriptional change in ILV5. It appears that the response to cold temperature may be strongly influenced by strain, medium and exact temperature used.…”
Section: Discussioncontrasting
confidence: 81%
“…In a proteomic study of the response of the same wine yeast at low temperature, Salvadó et al . [30] also detected a higher concentration of Yhb1 (Yeast hemoglobin-like protein), with functions in oxidative stress response.…”
Section: Discussionmentioning
confidence: 97%
“…A metabolome analysis is a powerful tool to understand metabolic changes in response to different environmental conditions, such as cold temperatures. In past years, some attempts have been made to elucidate the cold response of the same wine yeast Sc using a variety of high-throughput methodologies, such as transcriptomics [21] or proteomics [30]. These metabolic changes could be due to temperature-mediated transcriptional and/or to post-transcriptional effects on yeast.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp26, together with Hsp12, is also induced at the protein level when low‐temperature wine fermentation is carried out (Salvado et al . ). Therefore, chaperones like Hsp26 are good molecular markers that mark stress under many biotechnological conditions.…”
Section: Stress Response During the Biotechnological Use Of Wine Yeasmentioning
confidence: 97%